Impact of California's safe patient handling legislation on musculoskeletal injury prevention among nurses. Issue 1 (25th November 2018) - Lee, Soo‐Jeong; Lee, Joung Hee; Harrison, Robert
Abstract : Background: This study evaluated the impact of California's safe patient handling (SPH) legislation on musculoskeletal injury prevention among hospital nurses. Methods: Two serial cross‐sectional surveys were conducted using postal and online questionnaires in statewide random samples of California registered nurses in 2013 and 2016. Analysis included hospital nurses who performed patient handling ( n = 254 and n = 281, respectively). Results: In 2016, there were significant improvements in nurses' knowledge of a SPH policy in their hospital (87%), receipt of annual SPH training (73%), and availability of lift equipment (80%); 33% perceived their hospital's SPH programs as excellent or very good. Significant prevalence reduction was observed for work‐related musculoskeletal symptoms (61% vs 52%; Adjusted Prevalence Ratio = 0.78, 95% CI 0.66‐0.91). Conclusions: Our findings indicate the significant role of SPH legislation with positive impacts on SPH policies and programs at the hospital level and on musculoskeletal health outcomes at the worker level.